Peningkatan Hasil Belajar Mahasiswa Kelas Agribisnis 4 Fakultas Pertanian Umsu Mata Kuliah Penyuluhan Pertanian melalui Media Pembelajaran Video - Thamrin, Muhammad; Surnaherman, Surnaherman; Riza, Sri Mona (Universitas Negeri Medan, 2015)
This research is the classroom action research (PTK). It is held toward students of Department of Agribusiness 4 semester sixth of academic year 2014/2015 Faculty of Agriculture North Sumatra Muhammadiyah University, which is amount 40 persons. The research aims to improve the studentâs learning result that in the low level and did not achieve the minimum completeness criteria (KKM) of 65 score. This classroom action research uses learning media of video which is used as instrument to motivate the students in the learning process so that the learning result become better and achieve the score of KKM. The instruments are used by researcher is the 20-questions-multiple-choice and 5-question-essay test, observation sheet either for researcher or students, and using media of video. The studentâs learning result of the first cycle is the highest score of 78 and the lowest score 56. While the studentâs learning result in the second cycle obtaining the highest score of 88 and the lowest score of 68. The average score of first cycle is 68.65 experienced an increase in the second cycle with the average score of 81.15. This shows that learning media of video plays an important role in improving the studentâs learning result.